2007
DOI: 10.1186/1471-2164-8-394
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomic delineation of TLR-induced transcriptional networks

Abstract: Background: The innate immune system is the first line of defense mechanisms protecting the host from invading pathogens such as bacteria and viruses. The innate immunity responses are triggered by recognition of prototypical pathogen components by cellular receptors. Prominent among these pathogen sensors are Toll-like receptors (TLRs). We sought global delineation of transcriptional networks induced by TLRs, analyzing four genome-wide expression datasets in mouse and human macrophages stimulated with pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 47 publications
3
15
1
Order By: Relevance
“…The IRF and STAT (IRF1, IRF2, IRF4, IRF7, IRF8, IRF9, STAT1, STAT2, STAT3, STAT4 and STAT5A) genes were seen to be differentially regulated following LPS stimulation and the peak of their expression was at 6 hours. This difference in induction of IRF and STAT transcription regulators following TLR4 and not TLR2 ligation is consistent with previous studies which have compared the temporal transcriptional response following TLR2 and TLR4 ligation in murine DCs and macrophages [10], [11]. The IFN signalling induced following TLR4 ligation and not TLR2 ligation can be accounted for by signalling through the MyD88 independent TRIF-TRAM, IRF3 pathway following TLR4 ligation resulting in induction of IFNβ, which then leads to positive feedback of IFN gene induction through induction of IRF7 amongst other IRFs [8].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The IRF and STAT (IRF1, IRF2, IRF4, IRF7, IRF8, IRF9, STAT1, STAT2, STAT3, STAT4 and STAT5A) genes were seen to be differentially regulated following LPS stimulation and the peak of their expression was at 6 hours. This difference in induction of IRF and STAT transcription regulators following TLR4 and not TLR2 ligation is consistent with previous studies which have compared the temporal transcriptional response following TLR2 and TLR4 ligation in murine DCs and macrophages [10], [11]. The IFN signalling induced following TLR4 ligation and not TLR2 ligation can be accounted for by signalling through the MyD88 independent TRIF-TRAM, IRF3 pathway following TLR4 ligation resulting in induction of IFNβ, which then leads to positive feedback of IFN gene induction through induction of IRF7 amongst other IRFs [8].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally a separate IFN-sensitive response element (ISRE) regulated set of genes expression was seen to be upregulated in the TLR4 (and TLR3) stimulations but not the TLR2 stimulation [10]. Importantly the temporal kinetics of these two groups of genes differed, with the genes predicted to be regulated by NFκB peaking in expression earlier than the predicted ISRE regulated genes.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…47,48 Here, we show that TLR4 ligation increases hepcidin and represses ferroportin expression, while TLR2 ligation exclusively decreases ferroportin levels. To address the role of individual TLRs during the immune response most mechanistic studies apply synthetic ligands.…”
mentioning
confidence: 68%
“…First, Elkon et al (42) combined computational analysis of expression profiles and cis -regulatory promoter sequences to dissect the TLR-induced transcriptional program. Their model demonstrated that NF-κB mainly regulates an early-induced and sustained response, whereas the ISRE element functions primarily in the induction of a delayed wave.…”
Section: Systems Analysis Of Innate Immunity: Case Studiesmentioning
confidence: 99%